RECONSTRUCTING ISLAMIC ETHICAL REASONING IN DIGITAL GOLD INVESTMENT: A QUALITATIVE STUDY OF MUSLIM MORAL PERCEPTIONS - Yuwono, Cinanthya; Ghofur, Abdul (UIN Walisongo Semarang, 2025)
This study investigates the ethical perceptions of Muslim communities toward digital gold innovations in the era of financial digitization, emphasizing the integration of Islamic values, economic considerations, and modern financial technology. Unlike previous studies focusing primarily on economic factors or technology adoption, this research highlights the role of ethics, Sharia compliance, and social norms in investment decisions. Using a qualitative approach, data were collected through literature review and in-depth interviews with Muslim digital gold investors, allowing for a comprehensive understanding of ethical reasoning and value reconstruction in digital financial practices. The findings reveal that investors consider not only financial benefits but also principles such as justice (‘adl), trustworthiness (amanah), honesty (shiddiq), public interest (maslahah), and sincerity (ikhlas) when evaluating investment legitimacy. Digitalization is perceived as a means to facilitate accessible, efficient, and Sharia-compliant investment without compromising ethical principles. The study also indicates the importance of clear contracts, transparency, and credible Sharia certification in enhancing trust. These insights contribute to developing an ethical evaluation framework for Sharia fintech and provide guidance for designing digital financial products that are morally sound, socially beneficial, and financially secure. The results further suggest directions for future research on digital literacy, educational strategies, and social influence in shaping young Muslims’ investment behavior.